(untitled) (Tanzania Medical Journal, 2017)
We report a case of transient right ventricular dysfunction associated with prolonged cardiac tamponade, an unusual complication of uncertain etiology. We believe that in this case dynamic coronary flow restriction resulted in ischemic injury and stunning of the right ventricle. Other possible causes are briefly reviewed. Right ventricular failure can easily emerge undetected during tamponade since both disorders exhibit very similar physical findings. This complication should be considered when patients with pericardial effusion and tamponade deteriorate unexpectedly or fail to respond as anticipated following pericardial drainage. Our patient’s clinical course identifies a potential adverse event associated with delayed diagnosis and treatment of cardiac tamponade which should encourage prompt pericardial drainage at the earliest clinical sign of cardiac compression.